Penerapan Metode WP dan ROC dalam Pemilihan Siswa Peserta Olimpiade Sains - Dwika Asrani; Telaumbanua, Delis Marnyu; Aldi Chandra Maulana; Rima Tamara Aldisa (ADA Journal of Information System Research, 2024)
The organizers of the National Science Olympiad (OSN) aim to find talent, interest and learn to compete, increase knowledge in the field of science which is carried out once a year. The process of selecting prospective OSN participants who pass the selection is not an easy thing because the school has to select one student at a time. So that a decision support system for selecting prospective OSN participants is needed using the Weighted Product WP method to efficiently select prospective OSN participants. To select students who will take part in OSN using the Weighted Product WP and Rank Order Centroid ROC methods, use the criteria for subject scores (containing 6 subject matter) or those related to subject matter in OSN, academic achievement, OSN experience. The results obtained with the WP and ROC methods the school can efficiently recommend prospective participants who will take part in OSN because there is no need to select students one by one. . In this study, the highest ranking results were given to Alternative 2 named Bagas with a value of 0.261.